Quantified Estimation of Molecular Detections across Different Classes of Neptunian Atmospheres Using Cross-correlation Spectroscopy: Prospects for Future Extremely Large Telescopes with High-resolution Spectrographs - Dwaipayan Dubey; Liton Majumdar; Charles Beichman; Geoffrey A. Blake; Gautam Vasisht; Thomas Henning (The Astrophysical Journal Supplement Series)
Neptune-size exoplanets are less studied as characterizing their atmospheres presents challenges due to their relatively small radius and atmospheric scale height. As the most common outcome of planet formation, these planets are crucial for understanding planetary formation, migration theories, atmospheric composition, and potential habitability. Their diverse atmospheres, influenced by equilibrium temperature, composition, and cloud presence, offer unique opportunities to study atmospheric dynamics and chemistry. While low-resolution spectroscopy struggles with atmospheric characterization due to clouds, high-resolution observations provide detailed analysis of the atmospheres by detecting molecular lines beyond the cloud deck. This study investigates four subclasses of Neptune atmospheres: HAT-P-11 b (warm Neptune), HD 63433c (warm sub-Neptune), K2-25 b (temperate Neptune), and TOI-270 d (temperate sub-Neptune), using six ground-based spectrographs: GIANO-B, CARMENES, IGRINS, HISPEC, MODHIS, and ANDES over one and three transits. Our simulation integrates the chemical kinetics model VULCAN with the 1D line-by-line radiative transfer model petitRADTRANS, and estimates detection significance using the ground-based noise simulator SPECTR. We aim to predict how future extremely large telescopes (ELTs) such as TMT (MODHIS) and E-ELT (ANDES) can utilize their higher resolving powers and larger collecting areas to surpass current observatories in detecting molecular bands. We highlight the importance of photochemistry in these atmospheres and demonstrate how ELTs will help further in constraining nitrogen and sulfur chemistry. Finally, we present a comprehensive picture of cloud presence in the atmospheres and its impact on molecular detectability in Neptune-class atmospheres.